Attempts to Create Products with Increased Health-Promoting Potential Starting with Pinot Noir Pomace: Investigations on the Process and Its Methods - Stephen Lo; Lisa I. Pilkington; David Barker; Bruno Fedrizzi (Foods, 2022)
A process for using grape (Pinot noir) pomace to produce products with improved health-promoting effects was investigated. This process integrated a solid–liquid extraction (SLE) method and a method to acylate the polyphenolics in the extract. This report describes and discusses the methods used, including the rationale and considerations behind them, and the results obtained. The study begins with the work to optimize the SLE method for extracting higher quantities of (+)-catechin, (−)-epicatechin and quercetin by trialing 28 different solvent systems on small-scale samples of Pinot noir pomace. One of these systems was then selected and used for the extraction of the same flavonoids on a large-scale mass of pomace. It was found that significantly fewer quantities of flavonoids were observed. The resultant extract was then subject to a method of derivatization using three different fatty acylating agents. The antiproliferative activities of these products were measured; however, the resulting products did not display activity against the chosen cancer cells. Limitations and improvements to the methods in this process are also discussed.